Investigating the effective factors on the duration of breast feeding - F Jamshidi Evanaki; Sh Golyan Tehrani; Gh Babaie; T Hadyan (Tehran University of Medical Sciences, 2004)
Introduction: A balanced and proper diet is an essential factor in maintaining individual's health. The improvement of feeding in different age groups, especially children, is considered a significant step in primary health care. Materials and Methods: This research is a descriptive and analytic study. A sample of 225 mothers whose babies were between 0-24 months and who were referred to selected centers were chosen, using random sampling. The tool was a questionnaire. To analyze the data, the descriptive statistical, frequency distribution charts, the mean and central tendency as well as inferential statistics (2 test and Pearson correlation) were applied.    Results: The findings of the research showed that there is a meaningful relation between variables of age, occupation, the method of the last delivery, inclination of mother to the breast feeding, age of fetus at the time of birth, hospitalization of the neonate, the time of first breast feeding after the childbirth, the quality of baby's nutrition while he is hospitalized, the quality of the baby's first nutrition, the time of starting aid-feeding, using the aid-milk and using the pacifier by the baby with the duration of breast feeding. Such a relationship was also found between husband's idea about the breast feeding, examination of the breast during the pregnancy, teaching the advantages of the breast feeding and its correct method during the pregnancy, the place of the last childbirth, teaching the importance and the correct method of breast feeding after the childbirth, an encouraging and supporting husband concerning breast feeding, presence of the mother and the baby in a same-room after the childbirth, manner of arranging the intervals and times of the breast feeding, breast feeding during the night, renewed pregnancy and the duration of breast feeding in each session with the duration of breast feeding. Conclusion: According to the findings of the research, different factors affect duration of the breast feeding. Necessity of the midwife's attempt to instruct mothers during pregnancy and after childbirth was affirmed. The necessity of instruction of the medical groups about breast feeding is also made clear more than before.